2007
DOI: 10.1111/j.1538-7836.2007.02566.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism 10034C>T is located in a region regulating polyadenylation of FGG transcripts and influences the fibrinogen γ′/γA mRNA ratio

Abstract: To cite this article: Uitte de Willige S, Rietveld IM, de Visser MCH, Vos HL, Bertina RM. Polymorphism 10034C>T is located in a region regulating polyadenylation of FGG transcripts and influences the fibrinogen c¢/cA mRNA ratio. J Thromb Haemost 2007; 5: 1243-9.Summary. Background: Fibrinogen gamma haplotype 2 (FGG-H2) is associated with reduced fibrinogen c¢ levels and fibrinogen c¢/total fibrinogen ratios and with an increased deepvenous thrombosis (DVT) risk. Two FGG-H2 tagging single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…This haplotype includes two SNPs in the intron 9/exon 10 region (Figure 1), FGG 9615C > T (rs2066864) and FGG 10,034C > T (rs2066865). The 10,034T allele is located within a GT-rich downstream sequence element in a potential cleavage stimulation factor binding site, and has been shown to decrease the ratio of γ ′ / γ A mRNA in a minigene construct (44) . The 10,034T allele has also been associated with decreased γ ′ fi brinogen levels and a decreased γ ′ fi brinogen/total fi brinogen ratio (34) .…”
Section: γ ′ Fibrinogen and Arterial Thrombosismentioning
confidence: 99%
“…This haplotype includes two SNPs in the intron 9/exon 10 region (Figure 1), FGG 9615C > T (rs2066864) and FGG 10,034C > T (rs2066865). The 10,034T allele is located within a GT-rich downstream sequence element in a potential cleavage stimulation factor binding site, and has been shown to decrease the ratio of γ ′ / γ A mRNA in a minigene construct (44) . The 10,034T allele has also been associated with decreased γ ′ fi brinogen levels and a decreased γ ′ fi brinogen/total fi brinogen ratio (34) .…”
Section: γ ′ Fibrinogen and Arterial Thrombosismentioning
confidence: 99%
“…Because FGG-H2 SNPs 10034C3T and 9615C3T [rs2066864] are completely linked, the functionality of these SNPs on ␥A/␥Ј fibrinogen expression was investigated using mini-gene constructs. 98 This study concluded that 10034C3T is responsible for the reduction in ␥A/␥Ј fibrinogen level since this SNP is located in a GT-rich downstream sequence element, which composes a putative cleavage stimulation factor binding site and regulates the usage of the 2 polyadenylation signals in FGG. How FGG-H3 influences ␥A/␥Ј fibrinogen expression is still unknown, but as SNP 9340T3C is situated in intron 9, it may be that this variation somehow also regulates the 2 polyadenylation signals in FGG.…”
Section: Determinants Of the ␥A/␥ Fibrinogen Levelmentioning
confidence: 99%
“…This notion was confirmed with the finding of APC resistance. Individuals from families with protein S, protein C, or antithrombin deficiency but also APC resistance had a higher risk for VTE when they inherited combined defects rather than only one defect (Koeleman et al, 1994;van Boven et al, 1996). Thus, the penetrance of thrombosis increases in these protein C deficient families after introduction of the factor V Leiden allele in the pedigree (Brenner et al, 1996).…”
Section: Thrombophilia As Oligogenetic Diseasementioning
confidence: 99%
“…In particular subtype IIb confers a lower risk than the other subtypes (Finazzi et al, 1987). Risk estimates for developing VTE in the presence of AT deficiency are mainly based on family studies and these show a 10-20 fold increased risk (Lijfering et al, 2009;Mahmoodi et al, 2010;van Boven & Lane, 1997). The risk for developing a recurrent VTE is 10.5% per year without long-term anticoagulant treatment.…”
Section: Antithrombin Deficiencymentioning
confidence: 99%
See 1 more Smart Citation